(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Empowering tribal women in India is crucial for achieving inclusive development and social equity. Tribal women face multiple challenges, including poverty, illiteracy, health disparities, and systemic discrimination. These issues are further compounded by cultural marginalization and a lack of access to resources. Social workers play a pivotal role in addressing these barriers through education, healthcare initiatives, economic empowerment programs, and advocacy for policy changes. This paper examines the contributions of social workers in uplifting tribal women, exploring case studies and community-based interventions that demonstrate successful outcomes. It also identifies barriers faced by social workers, such as cultural resistance, resource constraints, and policy gaps, while proposing strategies to enhance their impact. The findings underscore the importance of a multidimensional approach to social work that integrates grassroots mobilization, skill-building, and advocacy, paving the way for sustainable empowerment of tribal women in India.